La contratación de trabajadores extranjeros en el Peru: Procedimientos y convenios suscritos por nuestro país que facilitan la contratación - Ataca Ugaz, May Lin (2014)
Over the past years, our country has witnessed a great increase in the hiring of foreigners for work purposes. It is in this context that it becomes relevant what has been established by de Legislative Decree 689, the Act of Recruitment of Foreign Personnel.In the present article, the authors develop the legal framework of foreigner´s hiring in Peru, as well as its requirements, limits, migration procedures and its scope of application. A reference is also made to the International Covenants signed by our country regarding the topic. The authors conclude, however, that national regulation on the hiring of foreign personnel is insufficient and has alimited scope.